Mapas de guia de rota em automóvel para motoristas com deficiência na visão de cores - Oliveira, Renan Furlan de [UNESP] (2015)
In-Car Route Guidance and Navigation System (RGNS) have been designed to people with normal color vision. However, cartographic representations of these systems can be illegible for drivers with deficiency in color vision, commonly known as color blindness. Therefore, to understand certain information in maps of RGNS can be a complex task for this group of users. This work evaluates the subjective preference of a group of drivers with color vision deficiency by using cartographic representations of RGNS, which was designed for people with this kind of perceptual characteristic. In a preliminary step it was selected a color vision simulator that best represents the color vision of color blindness, the Color Oracle. Then a graphical design analysis of two route guidance systems indicated readability and noise characteristics. Subsequently, a set of maps was designed based on aspects of color perception of individuals with color vision deficiency, and principles of cartographic communication as well. The results of the design consisted of a single representation for a background and two colors to symbolize car, direction arrow maneuver and route, totaling eight different maps. The evaluation for the preference was carried out with a group of 14 drivers with color vision deficiency. Participants' opinions suggest legibility for all representations. Although there have been no significant differences in terms of preference for different representations, the results showed that there was a trend to prefer car and the maneuver arrow outline in blue and the route in black. According to comments, this representation allowed better differentiation, identification and interpretation of the thematic cartographic symbols, both in relation to figure and background. It is recommended to evaluate the usability of these cartographic representations considering efficiency and effectiveness...